Fats and oils : formulating and processing for applications - O'Brien, Richard D. (CRC Press, 2009)
Preface Raw Materials Fats and Oils Processing Fats and Oils Analysis Fats and Oils Formulation Shortening Types Baking Shortenings Frying Shortenings Dairy Analog Shortenings Household Shortenings Margarine Liquid Oils Quality Management Troubleshooting.